Water Pollution Source Identification Based on Real-Time Monitoring System in Siak River - Kadir, E.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Water is a natural resource that is required for basic human life, the pollution of water become more serious in major sources such as in the river, sea, lake, etc. This research analyzed and identified the exact source of pollution sources, due to the length of the river and many industrial and other potential sources of pollution. A system of water pollution detection installed and deploy in measurement points along the river that potential to contribute to pollution especially surrounding industrial emit their chemical and wastewater. Data collected from the sensor analyzed use algorithm to find and check the abnormal and behavior data changing by the time. There 6 sets of detection systems deployed around the river, especially in the heavy residential and industrial areas. Due to the longest river, this research only analyzed and identified the source of polluted water around the city of Pekanbaru which many people used the water including water supply companies. Location of sources pollution identified and the exact location found at the sensor node number 2 and 4 which indicated by abnormal reading data, various kind of material contained into river detected by the sensors system. To get the accuracy of the location due to many factors then improve the algorithm by training data and doing many iterations as well as increasing data from the sensor and repeat for many times to determine the source coordinate as in the map. Â© 2021 IEEE.